THE COMPOSITION OF BREAST MILK AND THE IMPACT OF MATERNAL LIFE FACTORS ON CHILDREN'S HEALTH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Breast milk is the most natural and perfect source of nutrition for a newborn. It is enriched with numerous macro- and microelements, as well as biologically active components that play a decisive role in the infant’s growth, development, and immune system formation. This article provides a detailed review of the chemical composition of breast milk, including macronutrients, vitamins, minerals, enzymes, immunomodulatory substances, and growth factors. Additionally, it analyzes how maternal lifestyle factors (diet, physical activity, environmental conditions, smoking, and others) influence the composition of breast milk. This information deepens the understanding of the importance of breastfeeding in infant care.